Reliable change indices for the Italian Edinburgh Cognitive and Behavioral ALS Screen (ECAS). Issue 3 (3rd April 2023) - Aiello, Edoardo Nicolò; Solca, Federica; Torre, Silvia; Carelli, Laura; Monti, Alessia; Ferrucci, Roberta; Verde, Federico; Ticozzi, Nicola; Silani, Vincenzo; Poletti, Barbara
Abstract: This study aimed at providing standardized regression-based (SRB) reliable change indices (RCIs) for the Italian Edinburgh Cognitive and Behavioral ALS Screen (ECAS). Thirty-one consecutive ALS patients undergoing the ECAS were followed-up (T1) at 6.5 ± 1 months ( range  = 5–8). Ceiling/floor effects, practice effect, and test–retest reliability were assessed. Each ECAS measure was regressed by stepwise-entering as predictors demographics, respective T0 scores, T0 disease duration and ALSFRS-R, retest interval, and progression rate (ΔFS) – i.e., (48 - ALSFRS-RT0 )/disease durationT0 in months. Ceiling effects were infrequently detected, no practice effect emerged and all ECAS measures were reliable at retest (except for Language and Visuo-spatial subscales). T0 scores predicted all ECAS measures except for the Visuo-spatial subscale. The availability of RCIs for the Italian ECAS will aid ALS-related clinical practice and research within the longitudinal dimension.